Acute gastroenteritis outbreak in a school associated with religious ceremony in Mirzapur District, Uttar Pradesh, India - Rajesh Sahu; A L Ray; A K Yadav; R Kunte; D S Faujdar; Working GroupFNx01 (Wolters Kluwer Medknow Publications, 2021)
Background: A suspected food-poisoning outbreak occurred in a residential school in Mirzapur, India, in February, 2017. Objective: We investigated the outbreak to find out the epidemiology and to identify the risk factors. Methods: A descriptive study followed by retrospective-cohort study was done to investigate the outbreak. Cases (defined as ≥3 or more loose stools in 24 h, abdominal pain, or vomiting with onset between February 1 and 4, 2017) were searched by reviewing sick/patient registers from school and nearby health facilities. Cases were also searched through active surveillance by visiting school hostels. Stool samples were sent for microbiological testing. Food sources and food handlers were also assessed. Results: Among 468 students, 204 cases were identified (44% attack rate) without any mortality. The median age was found to be 14 years (range: 10-18 years) and 59% were male. Relative risk with consumption of curd, apple, and panjiri (sweetened wheat flour) was found to be 15.4, 2.5, and 3.7, respectively. All these three food items were served as prasad, a religious offering. Only consumption of sweetened curd (adjusted odds ratio = 36.1, 95% confidence interval = 12.1-107.8) was significantly associated with gastroenteritis. No microorganism was isolated from two tested stool samples. Curd from the vendor was prepared from nonpasteurized milk. There were no illnesses among food-handlers. Conclusions: This outbreak of acute gastroenteritis in a residential school was associated with consumption of curd, likely contaminated with preformed toxins. We recommend implementation of the food safety and standards authority of India regulations.